2022
DOI: 10.2147/jmdh.s366470
|View full text |Cite
|
Sign up to set email alerts
|

Time to Death and Predictors Among Neonates with Esophageal Atresia in Ethiopia

Abstract: Background Esophageal atresia is an upper gastrointestinal tract developmental abnormality in which the upper and lower esophagus do not connect. Esophageal atresia has a higher incidence of death in sub-Saharan Africa, ranging from 30% to 80%. In Ethiopia, infants with esophageal atresia had a higher mortality rate. The assessment of time to death and predictors of esophageal atresia can help to reduce newborn mortality. Objective This study was aimed to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Neonates diagnosed as having TEF were more hazardous than those neonates who did not have. In this study, about 24.6% of neonates were died due to diagnosed TEF, which is consistent with previous study ( 40 ). Neonates with this condition potentially develop aspiration and faced feeding difficulties resulting in low calories and immunity which affect their growth and development.…”
Section: Discussionsupporting
confidence: 93%
“…Neonates diagnosed as having TEF were more hazardous than those neonates who did not have. In this study, about 24.6% of neonates were died due to diagnosed TEF, which is consistent with previous study ( 40 ). Neonates with this condition potentially develop aspiration and faced feeding difficulties resulting in low calories and immunity which affect their growth and development.…”
Section: Discussionsupporting
confidence: 93%
“…The difference could be explained by the advanced surgical and medical care provided to newborns with esophageal atresia in western nations. Additionally, one factor contributing to the greater fatality rate in the TASH context may be the lack of complete parenteral nutrition (TPN) and mechanical ventilation in the NICU of TASH [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dehydration: Neonates with EA who had signs and symptoms of dehydration and documented on the medical chart as dehydration. Sepsis: Neonates with EA who had signs and symptoms of infection and documented on the chart as sepsis [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Brazilian study showed that advanced disease and surgical complications were the most common causes of death among perioperative patients (Meara et al 2016 ). One multinational LIC study on a 7-day cohort of perioperative outcomes put forward cardiovascular complications as the leading cause of death (Misganaw et al 2022 ). Regardless, septic shock was the most predominant cause of death in the surgical population.…”
Section: Discussionmentioning
confidence: 99%